TOWARDS THE ONTOLOGICAL PERSPECTIVE OF UNDERSTANDING PEDAGOGICAL AUTHORITY - Barbierato, Cristiana (Acta Paedagogica Vilnensia, 2015)
In academic works on authority in the tradition of educational sciences and philosophy, a dual tendency can be noted. Alongside authors who view authority with suspicion and treat it as limiting a person and not allowing the unfolding of his personality, there are those who consider authority as a positive phenomenon. However, the latter also do not always manage to reach the depth of the phenomenon of authority. The paper concentrates on the concepts of authority, formulated by philosophers and education scientists that, going back to the etymology of the word “authority”, not only consider the authority as a positive phenomenon in the vast life of the society and of a person and a positive factor in the process of education, but also give an ontological grounding for it. In this way the authority is considered as “authority that promotes growth”, that corresponds to the human nature because “someone else”, the encounter with “otherness” gives the possibility to be oneself. Three fundamental characteristics of authority have been highlighted: authority that implies an obedience in which men retain their freedom, the transcendental nature of authority, and authority as assuming responsibility and introducing the pupil to the depth of reality. Existential / personal “insight” is presented based on the thoughts of Arendt, Zambrano and Giussani and has shown a new way of looking into the contemporary status of pedagogical authority which is firstly characterized by the educator being lost on the level of Being. This ontological insight of the phenomenon of authority has important implications towards the educator and the pupil. It reminds the educator that the fundamental part of his task is not only the professional actions and functions, that his mission goes beyond rendering knowledge, and that he is a representative of “other” (culture, tradition, past...), obliged to transmit to the pupil “the wealth” that he himself has received. It also reminds the pupil that this education is essential because a person grows and becomes himself when “encountering the otherness”.
Keywords: pedagogical authority; authority that promotes growth; transcendental nature of authority; ontological perspective